Altered expression of noncanonical Wnt pathway genes in paediatric and adult adrenocortical tumours. (19th May 2014) - Mermejo, Livia M.; Leal, Leticia F.; Colli, Leandro M.; Fragoso, Maria C.B.V.; Latronico, Ana C.; Tone, Luiz G.; Scrideli, Carlos A.; Tucci, Silvio; Martinelli, Carlos E.; Yunes, Jose A.; Mastellaro, Maria J.; Seidinger, Ana L.; et al.
Summary Context The role of planar cell polarity (Wnt/PCP) and calcium‐dependent (Wnt/Ca) noncanonical Wnt pathways in adrenocortical tumours (ACTs) is unknown. Objectives To investigate the gene expression of Wnt/PCP and Wnt/Ca pathways and its association with TP53 p.R337H and CTNNB1 mutations in paediatric and adult ACTs and to correlate these findings with clinical outcome. Patients Expression of noncanonical Wnt‐related genes was evaluated in 91 ACTs (66 children and 25 adults) by qPCR and the expression of beta‐catenin, P53 and protein effectors of Wnt/Ca (NFAT) and Wnt/PCP (JNK) by immunohistochemistry. TP53 and CTNNB1 genes were sequenced. Results TP53 p.R337H mutation frequency was higher in children (86% vs 28%), while CTNNB1 mutation was higher in adults (32% vs 6%). Mortality was higher in adults harbouring TP53 p.R337H and in children with CTNNB1 mutations. Overexpression of WNT5A, Wnt/Ca ligand, was observed in children and adults. Overexpression of MAPK8 and underexpression of PRICKLE, Wnt/PCP mediators, were observed in paediatric but not in adult cases. Cytoplasmic/nuclear beta‐catenin and P53 accumulation was observed in the majority of paediatric and adult ACTs as well as NFAT and JNK. Overexpression of MAPK8 and underexpression of PRICKLE were associated with mortality in children, while overexpression of WNT5A and underexpression of PRICKLE were associated with mortality in adults. Conclusions In our study, TP53 p.R337H and CTNNB1 mutations correlated with poor prognosis in adults and children, respectively. We demonstrate, for the first time, the activation of Wnt/PCP and Wnt/Ca noncanonical pathway genes, and their association with poor outcome in children and adults, suggesting their putative involvement in ACTs aggressiveness.